SPORTSKO JEDRENJE U CRNOJ GORI - TRADICIJA, SADAŠNJOST I PERSPEKTIVA - Božidar Petričeić; Branislav Stjepčević; Borislav Roganović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
The navigation, as a predecessor of a sailing sport, all-round here had a big tradition and a deep root too. The oldest written document on those activities date from the beginning of the last Millenium. From its very first steps, in a certain way a navigator's rivalry, how to arrive before the others, was present, and with a time flow that fact becomes more and more important. The sailing, as an Olympic and an internationally recognized sport in Montenegro were organized in the Year 1948. In that time from 4 sailing clubs in the Boka KotorskaBay it was formed the Maritime Alliance of Montenegro, been renamed later into the Sailing Alliance of Montenegro. From its start our sailing alliance through the National Sailing Federation, now the SF of the State Community Serbia & Montenegro it has been incorporated in the International Sailing Federation (ISAF). The actual situation in the Montenegrin sailing sport characterizes an arising number of the sailing clubs, and now there are 10 of them. But, there is also a diminution of the number of the classes of the sport sailing boats. Now, in official use we have the Optimist, Laser, Star and the Cruiser class. Lately, the number of the Optimist class boats is in augmentation, which allow for more young kids to sail. Development of the sailing sport in Montenegro should be conducted simultaneously in a few directions. One of them is that the sailing clubs must be supported to their activities for own roomy, infrastructural and financial progress, with a purpose to improve proper sport work. A better perspective of a sailing sport also could be made with appropriate changes of a Race system (Match Race Regattas etc), and that is not all what could be done. It's very important, for the better perspective of a sailing sport in Montenegro, should build a very suitable National Sailing - Nautical Center. Realization of this initiative, which unfortunately goes quite slowly, would give a strong impulse for different activities within the sailing clubs. Also, would be given possibility to organize in Montenegro the regattas at the European and worldwide level for majority of the international and the Olympic class of the sailing boats.